Structural, Electronic, Molecular Orbital Analysis and Charge Distributions on Nitrate Salt of Guanidine through DFT and TD-DFT Methods - Thangarasu, S.; Siva, V.; Shameem, A.; Murugan, A.; Athimoolam, S.; Asath Bahadur, S. (Asian Journal of Chemistry, 2021)
Guanidinium nitrate, a non-linear optical material has been systematically studied through quantum chemical (density functional theory and Hartree Fock) methods. Studies on Mulliken charge, Frontier molecular orbitals (FMOs) and hyperpolarizability analyses have been performed. The Mulliken population analyses were carried out for the optimized molecular geometry by HF and B3LYP methods with 6-311++G(d,p) levels. The molecular orbital parameters of guanidinium nitrate have been calculated by FMO analysis. Frontier molecular orbital (FMO) analysis indicates the electron delocalization on the guanidinium nitrate and also its low value of energy gap indicates electron transfer. Optical property has been investigated by time-dependent density functional theory (TD-DFT) calculation. The second-order hyperpolarizability value of the ion pairs is much greater than urea, which confirms the good NLO nature of guanidinium nitrate.